Motivasi dan Praktik Spiritual Mahasiswa Mualaf: Studi Kasus di Lingkungan Universitas Muhammadiyah Palangkaraya - Marhani, Isnaeni; Hafid, Istiqamah; Arnisyah, Siti (NALAR, 2022)
AbstractSpiritual motivation is related to the fulfillment of spiritual needs such as self-actualization and individual tendencies to a particular religion, while spiritual practice is the embodiment of an individual's spiritual soul based on his spiritual awareness and experience. This study aims to determine the motivation and spiritual practice of students who converted to Islam while in college. The research design used is a qualitative case study approach involving four subjects with data collection techniques used are interview, observation and documentation. The results of the study found that two subjects had spiritual motivation before becoming a student, while the spiritual motivation of the other two subjects appeared when they were in college, which was motivated by the impressed factor by the worship practices of the academic community in college, as well as the understanding of Islam obtained from the Kemuhammadiyahan course. The subjects also experienced various dynamics and consequences after converting to Islam. It is known that three subjects received inconvenience treatment from their family and environment in the form of opposition, threat, insult, exile, not being given living expenses until they were kicked out of the house. While one subject gets a positive thing, namely the relationship with her parents is getting more harmonious. The spiritual practice has been carried out with full awareness by the four subjects. One of the four subjects is still actively following spiritual guidance while the other three subjects are no longer receiving spiritual guidance. They rely on manuals obtained when converting to Islam and seek information from the internet whenever they have in-depth questions about Islamic teachings.Keywors: Spiritual Motivation;